FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH MENGGUNAKAN PRODUK GADAI EMAS DI BANK SYARIAH MANDIRI KCP POLEWALI - Jumiarni Jumiarni; Moh. Yasin Soumena; Rusnaena Rusnaena (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2019)
This study aims to find out if the factors that consisting of factors promotion, factors influential damage value services and factors of the decision to use the customers gold pawn in a bank syariah mandiri as well as to know whether the most commonly the influential between promotion , services and factors factors value assessment of the decision to use the customers gold pawn in a bank syariah mandiri kcp polewali .The research is quantitative research with the methods descriptive .As for the data collection was done through the distribution of the questionnaire The methodology that was used to test hypotheses is by using the practical , reliability test , normality test , of multiple regression analysis , t test , test f , the coefficient of determination ( adjusted r square ) , and correlations double .Based on the research done it can be seen that the regression equation is linear research and the worship of idols in this is y: 3,138 + 0,141x1 + 0,270x2 + 0,407x3, The results of the testing simultaneously ( f ) variable x consisting of the x1 ) ( promotion , the service ( ) x2 , and the damage the x3 ( ) led to a positive and significant of the decision of customers to use the gold pawn of significantly by 0,000; 0,05 & it .Then , the results of the test on this fact ( ) suggests that the variable t ( service x2 ) value assessment and the x3 ( ) most dominant influence simultaneously with the resolution of customers to use the gold pawn , it is spotted with significant value and 0,000 0,006; 0,05 & it .